Pelatihan Ecoprint Teknik Steam bagi Ibu-Ibu PKK Desa Sempulur sebagai Alternatif Peluang UMKM - Sugiyanto Sugiyanto; Fika Maulydha Hardiyanti; Fitria Nur Azizah; Nova Yunita; Setya Aji Pratama (Jurnal Bina Desa, 2026)
The sustainability of MSMEs is a challenge that must be faced amid the onslaught of global products. The development of MSMEs must continue to be encouraged through various empowerment programs that focus on improving the skills and creativity of business actors. The purpose of the service of the UNNES GIAT 9 Team in Sempulur Village is to provide new skills that are easily applied at home and can produce products with high selling value. Meanwhile, this service is aimed at PKK women in Sempulur Village, Karanggede District, Boyolali Regency. The method used in this service is the direct observation method with the method of implementing training directly to the service location at Sempulur Village Hall, Karanggede District, Boyolali Regency by means of steam technique ecoprint training in making motifs on tote bags. The results of the team's work program were well received by the PKK women. This ecoprint training has also been implemented to impact the sustainability of Sempulur Village MSMEs. This was evidenced in the implementation of the MSME expo in Karanggede Subdistrict which was lively with many MSME products displayed, as well as the implementation of the MSME expo in Sempulur Village itself.